1986
DOI: 10.1007/bf00165587
|View full text |Cite
|
Sign up to set email alerts
|

Laser microsurgery: A review of 105 intracranial tumors

Abstract: The relative importance or utility of the carbon dioxide laser within the total context of multimodality therapy and in comparison to conventional surgical techniques is unknown. Over a 36 month period, 421 operations for tumors of the brain and spinal cord were performed in our clinic. Of these, 111 (26%) were carried out with the aid of the laser. After excluding stereotactic and transsphenoidal operations, a comparison was made between 105 laser and 216 non-laser craniotomies. With the exception of pituitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It is most valuable when used to resect deep, relatively avascular tumors which must be approached through small cortical incisions to protect neurologic function. A radical excision of a glial tumor can be satis factorily accomplished in virtually any hemispheric lo cation using proper technique [24] and the use of the in strument is generally felt to make surgery safer and faster, but this has not been demonstrated statistically [24], Similarly, although use of the laser has permitted more aggressive resections of astrocytomas than con ventional techniques, it is difficult to say whether this has improved longevity.…”
Section: Surgerymentioning
confidence: 99%
“…It is most valuable when used to resect deep, relatively avascular tumors which must be approached through small cortical incisions to protect neurologic function. A radical excision of a glial tumor can be satis factorily accomplished in virtually any hemispheric lo cation using proper technique [24] and the use of the in strument is generally felt to make surgery safer and faster, but this has not been demonstrated statistically [24], Similarly, although use of the laser has permitted more aggressive resections of astrocytomas than con ventional techniques, it is difficult to say whether this has improved longevity.…”
Section: Surgerymentioning
confidence: 99%
“…Retrospective studies comparing the CO 2 laser to other techniques demonstrated an increased operative time, increased number of reoperations, and no change in outcomes (except in the case of meningiomas located in functional regions). 30,31 The advent of the flexible OmniGuide fiber has enhanced the utility of the CO 2 laser, overcoming ergonomic obstacles that limited the efficient use of line-of-sight CO 2 lasers. Reports of Omni-Guide CO 2 laser use in the surgical management of numerous central nervous system pathologies has recently been described.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 321 intracranial tumors, 105 of which were treated with a line-of-sight CO 2 laser, Salcman et al (41) found no significant difference between laser and nonlaser groups in terms of mortality, CNS morbidity, blood loss, or length of hospital stay. The number of reoperations in the laser group (60.1%) was greater than in the nonlaser group (32.7%), as was mean operative time (299 minutes vs 237 minutes) (41).…”
Section: Clinical Studiesmentioning
confidence: 98%
“…In a review of 321 intracranial tumors, 105 of which were treated with a line-of-sight CO 2 laser, Salcman et al (41) found no significant difference between laser and nonlaser groups in terms of mortality, CNS morbidity, blood loss, or length of hospital stay. The number of reoperations in the laser group (60.1%) was greater than in the nonlaser group (32.7%), as was mean operative time (299 minutes vs 237 minutes) (41). In a similar study of 198 gliomas and 220 meningiomas operated on with either laser or conventional techniques, Lombard et al (31) found laser treatment to be associated with improved morbidity and quality of life in patients with glioma after resection.…”
Section: Clinical Studiesmentioning
confidence: 98%